2007
DOI: 10.1016/j.amjhyper.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hypertension, Cardiovascular Damage and Endothelial Dysfunction with Green Tea Extracts

Abstract: The GTE prevented hypertension and target organ damage induced by a high Ang II dose, likely by prevention or scavenging of superoxide anion generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 29 publications
5
38
0
Order By: Relevance
“…Green tea has been found to reduce plasma concentrations of oxidized LDL, 10,26 which may promote atheroma formation by increasing macrophage uptake, 27 monocyte recruitment 28 and direct endothelial cell damage. 29 Apart from the antioxidant and lipid-lowering effects, many other mechanisms may be responsible for the protective effects of green tea in the process of atherogenesis, which include a beneficial effect on hypertension, 11,12 improvement of hemorheological abnormalities, 13 inhibition of platelet aggregation 14,15 and improvement of endothelial function, 16,17 which plays an important role in the first step toward coronary arteriosclerosis. 30 Few studies conducted in Japan have reported the relationship between green tea consumption and angiographically proven CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green tea has been found to reduce plasma concentrations of oxidized LDL, 10,26 which may promote atheroma formation by increasing macrophage uptake, 27 monocyte recruitment 28 and direct endothelial cell damage. 29 Apart from the antioxidant and lipid-lowering effects, many other mechanisms may be responsible for the protective effects of green tea in the process of atherogenesis, which include a beneficial effect on hypertension, 11,12 improvement of hemorheological abnormalities, 13 inhibition of platelet aggregation 14,15 and improvement of endothelial function, 16,17 which plays an important role in the first step toward coronary arteriosclerosis. 30 Few studies conducted in Japan have reported the relationship between green tea consumption and angiographically proven CAD.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, another study has failed to show that green tea has protective effects. 6 The potential protective effect of green tea and tea constituents from CAD may be due to lipid-lowering, 7,8 antioxidative, 9,10 antihypertensive, 11,12 hemorheological abnormality-improving, 13 antithrombogenic 14,15 and vasculoprotective 16,17 activities. To our knowledge, until now there has not been any studies that have evaluated the relationship between green tea consumption and angiographically proven CAD in China.…”
Section: Editorial P 248mentioning
confidence: 99%
“…Two different techniques, which overall provide similar results, were used at the 2 participating centers. Arteries were investigated with the pressurized myography at the University of Padua 18 and with the wire myograph (410 A, Danish Myo-Technology) at the University of Brescia, as described. 10,12 For more details please see the data supplement.…”
Section: Evaluation Of Small Artery Structurementioning
confidence: 99%
“…Hence, as depicted in Figure 2, one or more genetic and/or environmental factors affecting the pathways through which aldosterone induces vasoconstriction or Na + and water retention can have an impact on the final phenotype BP in PA, as recently discussed. 6 For example, a low Na + intake and/or a high consumption of green tea, which lowers BP, 8 can mask the BP-raising effect of aldosterone, although this was unfortunately not assessed by Ito et al 2 Nonetheless, the occurrence of these interactions is best supported by the fact that normotensive PA has been documented in two patients with Bartter-Gitelman syndrome, a condition usually associated with Na + wasting and low BP. 9 …”
Section: Why Can Patients With Pa Be Normotensive or Only Mildly Hypementioning
confidence: 87%